Hot Tub Lung Mimicking Classic Acute and Chronic Hypersensitivity Pneumonitis: Two Case Reports. Issue 6 (2007) - Verma, Geetika; Jamieson, Frances; Chedore, Pamela; Hwang, David; Boerner, Scott; Geddie, William R; Chapman, Kenneth R; Marras, Theodore K
Abstract : Pulmonary disease in otherwise healthy patients can occur by secondary exposure to nontuberculous mycobacteria from hot tubs. The pathology of hot tub lung may be related to an infection, a hypersensitivity reaction or both. Previous reports of hot tub lung have highlighted distinct pathological features that have distinguished this entity from classic hypersensitivity pneumonitis. Two cases of hot tub lung in Ontario, which presented at very different time points in their disease course, are reported; one patient presented more fulminantly with a clinical picture resembling subacute hypersensitivity pneumonitis, and the other presented with chronic disease. Both cases exhibited clinical, radiological and pathological findings closely mimicking classic subacute and chronic hypersensitivity pneumonitis.